Perancangan Website Profil Sekolah Menggunakan Metode Waterfall (Studi Kasus : SMAS PGRI 22 Serpong) - Kesya Ayu Fatharani; Annisa Meliany Mumtaz; Adi Ranlam Hidayat; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
This research aims to design a profile website for SMAS PGRI 22 Serpong as a solution to the limitations of information dissemination, which has so far been done manually and inefficiently. The design is carried out using the Waterfall method through the stages of requirements analysis, system design, implementation, testing, and maintenance. The tools used in system development include XAMPP, Visual Studio Code, and StarUML for creating Use Case Diagrams, Sequence Diagrams, and Entity Relationship Diagrams. This website contains various important information such as the school profile, history, vision and mission, organizational structure, list of teachers and staff, majors, facilities, gallery, and download page. System testing shows that the developed system can replace the manual method and improve information accessibility to the public. Therefore, this school profile website is expected to become a modern and effective digital information medium.